A representação ficcional da violência sexual infantil na obra de Dalton Trevisan: 1959 a 2014 - Cestille, Mariana (2023)
Dalton Trevisan published works for more than half a century, from the middle of the 20th century to the beginning of the 21st century. These works of marital wars deal with urban problems and problems through the characters’ imagination. Among these problems, the theme of sexual violence against children is inserted. Therefore, this research sought to present, as a study proposal, an investigation of the fictional representation of child sexual violence in the work of Dalton Trevisan, published from 1959 to 2014. Thus, the study was organized in five moments. In the first moment, Trevisan’s trajectory in Brazilian literature was presented, which opened to the author’s critical fortune, such as the studies of Waldman (1976, 1982, 2013) and Sanches Neto (1996, 1998). The second moment turned to the construction of childhood, to understand the view of child’s construction from a literary conception. For that, the theories of Ariès (1986), Dourado (2009) and Engels (1884) were used. The third moment sought to understand the various discourses historically constructed about sex and sexuality, based on Foucault (1976, 1984, 2018). Based on the theorie of Berman (1982), the fourth moment presented a dialogue between the practices of violence and the urban context, highlighting the theme of modernization within the city that is the scene of the violence. Finally, from the chapters presented above, the persistence of the representation of child sexual violence in thirtynine fictions by Dalton Trevisan was investigated, to understand how the theme of violence unfolded in the writer’s work for more than fifty years of publication.